2010
DOI: 10.1136/oem.2010.056218
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of floor surface, shoes, floor cleaning and slipping in US limited-service restaurant workers

Abstract: These results provide support for the use of slip-resistant shoes and measures to increase COF as preventive interventions to reduce slips, falls and injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 40 publications
0
51
1
Order By: Relevance
“…Ideally all these aspects should be targeted to prevent accidents. In some situations use of proper footwear can be a feasible way to prevent slips (Verma et al 2011, McKiernan 2005. The participants in the present study however described dissatisfaction with both the shoes provided by the employer and the non-provision of working shoes.…”
Section: Criteria For a Slip-resistant Winter Shoecontrasting
confidence: 50%
“…Ideally all these aspects should be targeted to prevent accidents. In some situations use of proper footwear can be a feasible way to prevent slips (Verma et al 2011, McKiernan 2005. The participants in the present study however described dissatisfaction with both the shoes provided by the employer and the non-provision of working shoes.…”
Section: Criteria For a Slip-resistant Winter Shoecontrasting
confidence: 50%
“…The survey materials were made available in three languages: English, Spanish and Portuguese. Enrolment procedures have been previously described in detail 22 24…”
Section: Methodsmentioning
confidence: 99%
“…Three tiles were selected from each location, and two measurements were taken on each tile in the direction of traffic and parallel to the restaurant equipment 22 25. Floor COF was measured according to the F-1677-96 standard method published by the American Society for Testing and Materials,26 along with protocol refinements recommended by Chang 27.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dempsey and Filiaggi (2006) studied 100 restaurant food servers in the United States and found that 42% reported musculoskeletal problems, primarily in the back and shoulders; Kim et al (2013) found that 84% of restaurant workers reported musculoskeletal problems, with no significant distinction among job assignments within restaurants. Several studies (Dempsey and Filiaggi, 2006;Verma et al, 2011) found an elevated probability of slips and falls in the restaurant industry (specific profession undetailed).…”
Section: Physical Challengesmentioning
confidence: 99%